Manajemen Pengorganisasian Program Kursus Baca Kitab di Parappe: Program Kursus Baca Kitab - Rusdiman, Rusdiman B; Kamus; Z, Husna (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2023)
This article aims to analyze and describe the concept of learning management of read the turats course on Parappe about muzakarah and sorogan activity. This research use descriptive qualitative research method. Collection of data use interview technique. After collecting data, next step is parsing of data like filtering of data, describing of data and make a conclusion. From this research can known that organization managemet in read the turats institute of Parappe still weak because some obstacles like nor not yet clear organizational structure on read the turats institute of Parappe. Leader just give division of task orally to every member of organizational structure so that the position of leader and member is not clear.